1998
DOI: 10.1038/bjc.1998.710
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in advanced ovarian cancer: four systematic meta-analyses of individual patient data from 37 randomized trials

Abstract: Summary The purpose of this systematic study was to provide an up to date and reliable quantitative summary of the relative benefits of various types of chemotherapy (non-platinum vs platinum, single-agent vs combination and carboplatin vs cisplatin) in the treatment of advanced ovarian cancer. Also, to investigate whether well-defined patient subgroups benefit more or less from cisplatin-or carboplatinbased therapy. Meta-analyses were based on updated individual patient data from all available randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 28 publications
2
100
0
5
Order By: Relevance
“…First-line therapy constitutes optimal surgical debulking followed by administration of a platinum-based regimen. 144 Unfortunately, approximately 60-80% of patients relapse after initial treatment, and develop cisplatin resistance. 145,146 As such, Chang et al studied the ability of LB100 to sensitize ovarian cancer to cisplatin treatment using known cisplatin-resistant, p53-null (SKOV-3, OVCAR-8) cell lines as well as patient-derived cell lines harvested both prior to and after clinical development of cisplatin resistance.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…First-line therapy constitutes optimal surgical debulking followed by administration of a platinum-based regimen. 144 Unfortunately, approximately 60-80% of patients relapse after initial treatment, and develop cisplatin resistance. 145,146 As such, Chang et al studied the ability of LB100 to sensitize ovarian cancer to cisplatin treatment using known cisplatin-resistant, p53-null (SKOV-3, OVCAR-8) cell lines as well as patient-derived cell lines harvested both prior to and after clinical development of cisplatin resistance.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Carboplatin proved equally efficacious (in single and combination therapy) but significantly less toxic than cisplatin (5). At standard doses, carboplatin has fewer adverse effects on kidneys, the nervous system, or the auditory system, and patients who receive carboplatin report reductions in nausea and vomiting relative to levels experienced with cisplatin.…”
mentioning
confidence: 89%
“…Although no hard evidence for an overall survival advantage with platinum-based compounds was demonstrated until the 1990s (4,5), early studies revealed that cisplatin significantly improved disease-free survival and response rates when compared with then-standard treatments. Cisplatin was effective as a single agent and in combination regimens, resulting in the relatively popular first-line combination of cisplatin with cyclophosphamide.…”
mentioning
confidence: 99%
“…Patients who have had primary cytoreduction should receive chemotherapy following surgery [1,51] (Table 3). The accepted standard is 6 cycles of platinum-based combination chemotherapy, with a platinum (carboplatin or cisplatin) and a taxane (paclitaxel or docetaxel) [52][53][54][55][56].…”
Section: Chemotherapy For Advanced Stage Ovarian Cancermentioning
confidence: 99%